Radiation-induced breast angiosarcoma: a case report - Tato-Varela, Sara (Ecancermedicalscience, 2016)
Radiation-induced breast angiosarcoma is a severe but rare late complication in the breast-preserving management of breast cancer through surgery and radiotherapy [1]. Often the initial diagnosis of this entity is complex given its relatively anodyne nature and usually being present in the form of typically multifocal reddish-purple papular skin lesions [2]. Because of the low incidence of this tumour, there is a limited number of studies regarding its optimal therapeutic management [3]. The preferred treatment is aggressive surgical removal and the prognosis is poor with an overall survival rate of 12–20% at five years [4].